Supported hydrotreating catalysts having enhanced activity - Patents.com
Patent Information
- Application Number
- JP2024525920
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2021-11-05
- Filing Date
- 2022-11-04
- Publication Date
- 2024-12-23
AI Technical Summary
Existing hydroprocessing catalysts face challenges with low metal dispersion due to strong metal-support interactions, leading to reduced intrinsic activity and metal aggregation, particularly in calcined catalysts.
The development of supported catalysts using concentrated solutions of Group VI and Group VIII metals, incorporating chelating polymers within the support's pore structure, which enhances metal dispersion and activity through polymer modification, eliminating phosphorus as an impregnating additive and utilizing peroxomolybdocobaltate compounds.
The catalysts exhibit increased hydrodesulfurization and hydrodenitrogenation activities, suitable for hydrocarbon cracking pretreatment, with improved metal dispersion and stability, contributing to enhanced catalytic performance in hydroprocessing applications.
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to supported catalysts formed from concentrated solutions containing Group VI and Group VIII metals. [Background technology]
[0002] Various catalysts for hydrotreating, hydrodesulfurization, and / or hydrodenitrogenation are known and / or commercially available. Some of these catalysts contain molybdenum, nickel or cobalt, and phosphorus. Many of these catalysts are supported on a carrier and are usually prepared by pore volume impregnation. The art is continually striving to create different and better catalysts, especially with higher activity for hydrotreating, hydrodesulfurization, and / or hydrodenitrogenation.
[0003] Hydroprocessing catalysts are typically prepared by impregnation of a porous support material with a solution containing the active metals, followed by either drying or calcination. Calcined catalysts tend to exhibit strong metal-support interactions, resulting in high metal dispersion. However, it is theorized that the strong metal-support interactions in calcined catalysts result in weaker intrinsic activity of the catalyst. Uncalcined catalysts typically exhibit low metal-support interactions and inherently high activity. Due to the low metal-support interactions in uncalcined catalysts, the metals tend to agglomerate (poor metal dispersion). Summary of the Invention
[0004] The present invention provides a process for preparing supported catalysts from a concentrated solution containing group VI and group VIII metals, as well as catalysts prepared by such a process. Catalysts prepared according to the present invention exhibit high activity in hydrodesulfurization and hydrodenitrogenation. It has been suggested that in the polymer-modified catalysts of the present invention, the hydrogenation metals are more dispersed than in similar catalysts in the absence of polymer modification. A feature of the present invention is that the catalyst does not contain phosphorus as an impregnation additive. Another feature of the present invention is the peroxomolybdocobaltate compound that may be used in forming the phosphorus-free catalyst of the present invention. Increased catalytic activity is observed for catalysts according to the present invention where the catalyst is polymer-containing, compared to similar phosphorus-free catalysts that do not contain polymer.
[0005] Chelating polymers can be synthesized in the pore structure of support materials (e.g., inorganic oxides) in the presence of metals (e.g., Co, Ni, Mo). The presence of these chelating polymers enhances the activity of hydrotreating catalysts compared to catalysts that do not contain the polymer. Both hydrodesulfurization activity and hydrodenitrogenation activity are increased compared to catalysts that do not contain the polymer, making the catalysts of the present invention useful in a variety of hydrotreating applications, including, but not limited to, hydrocarbon cracking pretreatment (HC-PT), fluid catalytic cracking pretreatment (FCC-PT), and ultra-low sulfur diesel (ULSD).
[0006] An embodiment of the present invention is a supported catalyst. The supported catalyst includes a support, at least one Group VI metal, at least one Group VIII metal, and a polymer. In the catalyst, the molar ratio of the Group VI metal to the Group VIII metal is about 1:1 to about 5:1. The polymer in the catalyst has a carbon skeleton and includes a functional group having at least one heteroatom.
[0007] Another embodiment of the present invention is a peroxomolybdocobaltate compound containing cobalt and molybdenum in a cobalt:molybdenum ratio of about 0.5:2 to about 1.5:2.
[0008] Other embodiments of the present invention include processes for forming the above-described supported catalysts and the above-described peroxomolybdocobaltate compounds, as well as methods for hydrotreating, hydrodenitrogenating, and / or hydrodesulfurizing using the above-described supported catalysts.
[0009] These and other embodiments and features of the present invention will become further apparent from the following description, drawings, and appended claims. [Brief description of the drawings]
[0010] [Figure 1] 1 shows an FT-IR spectrum providing evidence of polymerization in the sample prepared in Example 4. [Figure 2-1] 1 shows a SEM-EDX linescan of a sample prepared as in Example 6. [Figure 2-2] 1 shows a SEM-EDX linescan of a sample prepared as in Example 6. [Figure 2-3] 1 shows a SEM-EDX linescan of a sample prepared as in Example 6. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] Throughout this specification, the phrases "hydrogenation metal" and "hydrogenation metals" refer collectively to Group VI metals or metals and Group VIII metals or metals. As used throughout this specification, the term "Group VI metal" refers to metals of Group VIB. As used throughout this specification, the phrases "as Group VI metal trioxide," "reported as Group VI metal trioxide," "calculated as Group VI metal trioxide," "expressed as their oxides," and similar phrases of Group VIII metals as their monoxides, refer to the amount or concentration of Group VI metal or Group VIII metal when the numerical value is the respective oxide, unless otherwise stated. For example, nickel carbonate may be used, but the amount of nickel is reported as the nickel oxide value. In contrast to common practice, the catalyst in the present invention does not contain phosphorus as an impregnation additive. Thus, the catalyst in the present invention may be referred to herein as a phosphorus-free catalyst. In some cases, phosphorus may be present in a functional group on the polymer of the catalyst.
[0012] As used throughout this specification, the term "impregnation," when referring to impregnation of a support, means that a substance, solution, or mixture penetrates into the pores of the support.
[0013] The impregnation solution used in the practice of the present invention comprises a solvent, at least one Group VI metal, and at least one Group VIII metal, with the molar ratio of Group VI metal to Group VIII metal being from about 1:1 to about 5:1.
[0014] The group VI metal is molybdenum, tungsten, and / or chromium, preferably molybdenum or tungsten, more preferably molybdenum. The group VIII metal is iron, nickel, and / or cobalt, preferably nickel and / or cobalt. A preferred combination of metals includes a combination of nickel and / or cobalt with molybdenum and / or tungsten. When the hydrodesulfurization activity of the catalyst is important, a combination of cobalt and molybdenum is advantageous and preferred. When the hydrodesulfurization activity of the catalyst is important, a combination of nickel with molybdenum and / or tungsten is advantageous and preferred. Another preferred combination of hydrogenation metals is nickel, cobalt, and molybdenum.
[0015] The Group VI metal compounds used to prepare the impregnation solution may be oxides, oxoacids, or ammonium salts of oxo or polyoxoanions, which are formally in the +6 oxidation state when the metal is molybdenum or tungsten. The oxides and oxoacids are preferably Group VI metal compounds. Suitable Group VI metal compounds in the practice of the present invention include chromium (III) oxide, ammonium chromate, ammonium dichromate, molybdenum trioxide, molybdic acid, ammonium molybdate, ammonium paramolybdate, tungsten trioxide, tungstic acid, ammonium metatungstate hydrate, ammonium paratungstate, and the like. Preferred Group VI metal compounds include chromium (III) oxide, molybdenum trioxide, molybdic acid, ammonium paratungstate, tungsten trioxide, and tungstic acid. Combinations of any two or more Group VI metal compounds may be used.
[0016] The Group VIII metal compounds used to prepare the impregnation solution are usually oxides, carbonates, hydroxides, hydroxycarbonates, or salts. Suitable Group VIII metal compounds include, but are not limited to, iron oxide, iron hydroxide, iron nitrate, iron carbonate, iron hydroxycarbonate, iron acetate, iron citrate, cobalt oxide, cobalt hydroxide, cobalt nitrate, cobalt carbonate, cobalt hydroxycarbonate, cobalt acetate, cobalt citrate, nickel oxide, nickel hydroxide, nickel nitrate, nickel carbonate, nickel hydroxycarbonate, nickel acetate, and nickel citrate. Preferred Group VIII metal compounds include iron hydroxide, iron carbonate, iron hydroxycarbonate, cobalt hydroxide, cobalt carbonate, cobalt hydroxycarbonate, nickel hydroxide, nickel carbonate, and nickel hydroxycarbonate. A combination of two or more Group VIII metal compounds may be used.
[0017] One or more organic additives are optionally included and can be non-acidic organic additives and / or acidic organic additives.
[0018] For non-acidic organic additives, the term "non-acidic" as used throughout this specification means that there are no acidic carboxylic acid groups in the additive. Non-acidic organic additives typically include compounds having at least two hydroxyl groups and 2 to about 10 carbon atoms, as well as (poly)ethers of these compounds. Some preferred non-acidic organic additives have two hydroxyl groups. Suitable types of compounds for non-acidic organic additives include fatty alcohols, ethers including ethers of fatty alcohols, polyethers, sugars including monosaccharides and disaccharides, and polysaccharides. Examples of such compounds include, but are not limited to, glycerin, trimethylolethane, trimethylolpropane, ethylene glycol, diethylene glycol, trimethylene glycol, triethylene glycol, tributylene glycol, tetraethylene glycol, tetrapentylene glycol, propylene glycol, dipropylene glycol, ethylene glycol monobutyl ether, diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, diethylene glycol monopropyl ether, diethylene glycol monobutyl ether, glucose, fructose, lactose, maltose, and saccharose. Preferred non-acidic organic additives include glycols such as diethylene glycol, triethylene glycol, and tetraethylene glycol. If desired, combinations of two or more organic additives may be used.
[0019] The optional acidic organic additive has at least one acid group and at least one functional group selected from a hydroxyl group and an acid group. Thus, at least, the acidic organic additive has one acid group and one hydroxyl group, or two acid groups. As used herein, the term "acid group" refers to a -COOH moiety. The acidic organic additive preferably has at least two carboxylic acid moieties and preferably has at least about three carbon atoms. It may be preferred that the acidic organic additive has at least one hydroxyl group. Suitable acidic organic additives include citric acid, gluconic acid, lactic acid, malic acid, maleic acid, malonic acid, oxalic acid, tartaric acid, and the like. Citric acid is the preferred acidic organic additive. A combination of acidic organic additives may be used.
[0020] The peroxomolybdocobaltate compounds of the present invention may be used to provide Group VI and Group VIII metals, where the Group VI metal is molybdenum and the Group VIII metal is cobalt, to form a catalyst according to the present invention. In forming the catalyst of the present invention, one or more Group VI and / or Group VIII metal compounds may be used in addition to the peroxomolybdocobaltate compound, although the use of a peroxomolybdocobaltate compound without additional Group VI or Group VIII metal compounds is preferred.
[0021] A polar solvent is usually required to dissolve the Group VI and Group VIII metal compounds or the peroxomolybdocobaltate compounds. In the present invention, the polar solvent can be protic or aprotic, and is generally a polar organic solvent and / or water. A mixture of polar solvents can be used, including a mixture containing an aprotic solvent and a protic solvent. Suitable polar solvents include water, methanol, ethanol, n-propanol, isopropyl alcohol, acetonitrile, acetone, tetrahydrofuran, ethylene glycol, dimethylformamide, dimethylsulfoxide, methylene chloride, and the like, and mixtures thereof. Preferably, the polar solvent is a protic solvent, and more preferably, the polar solvent is water or an alcohol, such as ethanol or isopropyl alcohol. A mixture of two or more polar solvents can be used. Water is the preferred polar solvent.
[0022] If the monomer and the carrier are combined and polymerized before contacting the impregnation solution (the solution containing the Group VI and Group VIII metal compounds, or the peroxomolybdocobaltate compound), the monomer may be polymerized in any solvent in which the monomer is soluble, including non-polar solvents. After polymerization, the solvent may be removed. If the monomer and the carrier are combined and polymerized before contacting the impregnation solution, removal of at least a portion of the solvent is preferred, especially if the polymerization solvent adversely affects the solubility of the Group VI and / or Group VIII metal compounds, or the peroxomolybdocobaltate compound. Suitable solvents for polymerization in the absence of the Group VI and / or Group VIII metal compounds, or the peroxomolybdocobaltate compound depend on the solubility of the monomer(s) used. The solvent(s) used in the polymerization step may be present in the solution with the Group VI and Group VIII metal compounds, or the peroxomolybdocobaltate compounds, so long as the solvent(s) from the polymerization step do not precipitate the Group VI and / or Group VIII metal compounds, or the peroxomolybdocobaltate compounds.
[0023] When the impregnation solution and the support are combined to form the impregnated support prior to contact with the monomer, the monomer may be dissolved in a solvent that may be the same as or different from the solvent of the impregnation solution. The solvent(s) of the monomer will depend on the solubility of the monomer(s) used. It is preferred to use the same solvent to dissolve the monomer and form the impregnation solution, although different solvents may be used if desired.
[0024] The solvent forming the impregnation solution must be capable of dissolving the Group VI and Group VIII metal compounds used to form the impregnation solutions used in the practice of the present invention, and such solvents are typically polar solvents.
[0025] When the monomer species, at least one Group VI metal compound, and at least one Group VIII metal compound are combined before polymerization, the monomer species should be soluble in the solution containing at least one Group VI metal compound and at least one Group VIII metal compound. When the impregnation solution contacts the support and the monomer species during polymerization, the same solubility considerations apply, i.e., the monomer species present should be soluble in the solution in the presence of at least one Group VI metal compound and at least one Group VIII metal compound. In many cases, in order for the monomer to be soluble in the solution containing the peroxomolybdocobaltate compound or at least one Group VI metal compound and at least one Group VIII metal compound, the monomer is at least somewhat soluble in the polar solvent in which the peroxomolybdocobaltate compound or the Group VI metal compound and the Group VIII metal compound are dissolved.
[0026] Throughout this specification, the term "monomer" is synonymous with the phrase "monomer species." A monomer species typically has 3 or more carbon atoms, preferably 3 to about 12 carbon atoms, more preferably 3 to about 10 carbon atoms, and even more preferably 3 to about 8 carbon atoms. A monomer species has at least one functional group containing carbon-carbon unsaturation and at least one heteroatom as a polymerizable moiety. It is theorized that the heteroatom(s) may form a bond or interaction with a metal ion, but the formation of a bond or interaction is not required. Preferred monomers include functional groups having one or more lone pairs of electrons. Preferably, the functional groups of the monomer species include nitrogen, oxygen, phosphorus, and / or sulfur. Examples of suitable functional groups include hydroxyl groups, carboxyl groups, carbonyl groups, amino groups, amide groups, nitrile groups, amino acid groups, phosphate groups, thiol groups, sulfonic acid groups, and the like. Preferred functional groups include hydroxyl groups, ester groups, amide groups, and carboxyl-containing groups, especially carboxylic acid groups, more preferably carboxylic acid groups and amide groups, especially amide groups.
[0027] Thus, suitable monomer species include acrylic acid, maleic acid, fumaric acid, crotonic acid, pentenoic acid, methacrylic acid, 2,3-dimethacrylic acid, 3,3-dimethacrylic acid, allyl alcohol, 2-sulfoethyl methacrylate, n-propyl acrylate, hydroxymethyl acrylate, 2-hydroxyethyl acrylate, 2-carboxyethyl acrylate, 3-ethoxy-3-oxopropyl acrylate, methylcarbamylethyl acrylate, 2-hydroxyethyl methacrylate, N-vinylpyrrolidone, acrylamide, methacrylamide, N-isopropylacrylamide, N-vinylacetamide, N-vinyl-N-methylacetamide, N-hydroxymethylacrylamide, N-hydroxyethylacrylamide, N-methoxymethylacrylamide, N-ethoxymethylacrylamide, vinyl sulfate, vinyl sulfonic acid, 2-propene-1-sulfonic acid, vinyl phosphate, vinyl phosphonate, dimethylallyl phosphate, diethylallyl phosphate, and the like. Preferred monomer species include acrylic acid, maleic acid, 2-carboxyethyl acrylate, acrylamide, and N-hydroxyethyl acrylamide. More preferred are acrylamide and acrylic acid, especially acrylamide. Two or more monomer species may be used, and when two or more monomer species are used, a copolymer is formed.
[0028] The amount of monomer used to form the catalyst of the present invention is expressed as a weight percent based on the total weight of the other components used to form the catalyst, excluding the solvent. As used throughout this specification, the phrases "other components used to form the catalyst" and "other catalyst components" refer to the support and chemicals that provide hydrogenation metals to the catalyst. For example, if the total weight of the other components of the catalyst (other than the solvent) is 100 grams, then 10 weight percent monomer is 10 grams. In the practice of the present invention, the amount of monomer is generally about 1.5 weight percent or more, preferably in the range of about 1.5 weight percent to about 35 weight percent, based on the total weight of the other components of the catalyst, including the support, the Group VI metal compound, and the Group VIII metal compound, although amounts outside these ranges are within the scope of the present invention, and the Group VI metal compound and Group VIII metal compound are expressed as their Group VI metal oxide and Group VIII metal oxide, excluding the weight of any solvent. More preferably, the amount of monomer is in the range of about 3% to about 30% by weight, even more preferably in the range of about 5% to about 25% by weight, and even more preferably in the range of about 10% to about 25% by weight, based on the total weight of the other components of the catalyst excluding the solvent.
[0029] In order to prevent premature polymerization of the monomer species, an inhibitor (e.g., a radical scavenger) may be included with the monomer. Suitable inhibitors will vary with the particular monomer(s). A suitable inhibitor will not adversely affect the at least one Group VI metal compound and the at least one Group VIII metal compound when present in the mixture before polymerization is initiated. Desirably, the inhibitor is neutralized or removed (e.g., by evaporation or introduction of an initiator) when it is desired to initiate the polymerization reaction.
[0030] The components used to form the impregnation solution may be combined in any order, but it is recommended and preferred that one component is suspended or dissolved in a solvent before the introduction of the other component. Preferably, the Group VIII metal compound is introduced first, and more preferably, the Group VI metal compound is introduced after the Group VIII metal compound. When forming the solution, stirring may be used, but may be stopped once the solution is homogeneous. Similar considerations apply when the monomer, at least one Group VI metal compound, and at least one Group VIII metal compound are combined, and it is preferred to combine the compound of the metal hydride with a solvent, usually a polar solvent, and then add the monomer.
[0031] Combining the components of the impregnation solution may be carried out at ambient conditions, i.e., room temperature and ambient pressure. Elevated temperatures may be required to facilitate dissolution of the components, particularly the Group VI and Group VIII compounds. Such elevated temperatures typically range from about 50°C to about 95°C, preferably from about 60°C to about 95°C. Temperatures above about 95°C and / or elevated pressures (e.g., hydrothermal preparation) may be applied, but are not required. If monomers whose polymerization is thermally initiated are included in the solution, the temperature to which the solution is heated is kept below the temperature at which polymerization is initiated, or, preferably, the monomer species is added after heating of the solution is completed.
[0032] It is convenient to prepare solutions having concentrations that are practical for the further intended use of the solution. These solutions can be used to form supported catalysts as embodied in the present invention. Suitable concentrations based on the Group VI metal (or the sum of the Group VI metals, if more than one metal is present in the composition) are typically in the range of about 1.39 mol / L to about 6 mol / L, preferably in the range of about 2.1 mol / L to about 4.2 mol / L.
[0033] Methods for preparing more concentrated impregnation solutions are known and are described, for example, in International Patent Publication No. WO2011 / 023668.
[0034] The impregnation solutions of the present invention, formed as described above, are solutions containing peroxomolybdocobaltate or Group VI and Group VIII metal compounds, or solutions in polar solvents. The concentrations of, and preferences for, the Group VI and Group VIII metals are as described above. In these solutions, the molar ratio of Group VI to Group VIII metals is from about 1:1 to about 5:1.
[0035] As mentioned above, when a combination of reagents is used to form the solution, a mixture of species with different metals will be present in the solution.For example, when a molybdenum compound and a tungsten compound are used, the product solution will contain molybdenum and tungsten.In another example, when a cobalt compound and a nickel compound are used, the solution will contain cobalt and nickel.A mixture of reagents such as Group VI metal compounds with different Group VI metals of the compound and Group VIII metal compounds with different Group VIII metals of the compound can be used to form the solution composition as needed.
[0036] The process of the present invention for forming a catalyst comprises: I) combining a support, one or more monomeric species, a solvent, and at least one Group VI metal compound and at least one Group VIII metal compound or peroxomolybdocobaltate compound in the following combination: a) a carrier, one or more monomeric species, and a solvent; b) a support, one or more monomeric species, and a peroxomolybdocobaltate compound or at least one Group VI metal compound and at least one Group VIII metal compound; or c) combining a support with an impregnation solution to form an impregnated support, and then combining the impregnated support with one or more monomer species; forming a monomer-containing mixture, the monomer species being soluble in a solvent and having at least one functional group containing carbon-carbon unsaturation and at least one heteroatom. When the polymerization initiator is a chemical, the initiator may be included in any of the combinations of a), b), and c) above in step I); step II) includes initiating polymerization of the monomer species in the monomer-containing mixture to form a polymerization product; step III) includes forming a monomer-containing mixture in I) similar to a) and A) contacting the monomer-containing mixture with an impregnation solution during the polymerization in II), or B) This is carried out when the process comprises contacting the polymerization product with an impregnation solution. A supported catalyst is formed. In this process, the molar ratio of group VI metal to group VIII metal is about 1:1 to about 5:1. The impregnation solution used in this process includes a polar solvent, at least one group VI metal, and at least one group VIII metal. Removal of excess solvent from the supported catalyst, for example by drying, is a recommended further step.
[0037] An initiator may be included in the above process. When used in the above process, the initiator may be introduced in a), b), or c). When combining the components as in c), the initiator is introduced after the impregnated support is formed.
[0038] A feature of the present invention is that there is little or no agglomeration of support particles in the process of the present invention for forming a catalyst, especially when a peroxomolybdocobaltate compound is used. The non-agglomerated catalyst particles produced are generally free-flowing and do not adhere to each other. When an initiator is used, a small amount of impregnation solution may leave the support and some polymer may form on the outside of the support, resulting in some agglomeration that is easily removed by applying minimal force (e.g., tapping with a hand) to any agglomerated particles. Another feature of the present invention is that the support particles are not altered in size and shape by the process of the present invention for forming a catalyst. For example, support particles having an average particle size of about 2 mm will result in catalyst particles having an average particle size of about 2 mm.
[0039] In the process of the present invention for forming a catalyst, all components in the impregnation solution must be dissolved before starting the impregnation step. If at least one Group VI metal compound and at least one Group VIII metal compound, or the peroxomolybdocobaltate compound, form part of a monomer-containing mixture, the monomer species are preferably combined with the mixture after any heating of the mixture has been terminated. In the case of a thermally initiated polymerization of monomers, the temperature during the formation of the monomer-containing mixture is kept below the initiation temperature for polymerization.
[0040] Since the polymerization reaction is usually exothermic, the reaction vessel must be heat resistant at least to the temperatures reached by the polymerization reaction.
[0041] In a preferred embodiment, the process involves forming an impregnation solution of a peroxomolybdocobaltate compound or a group VI metal compound and a group VIII metal compound in a polar solvent, optionally adding a thermally activated chemical initiator, then adding the support to the impregnation solution, followed by aging the mixture of the impregnation solution and the support at a low temperature (e.g., 30°C to 60°C) for a period of time, e.g., 0.5 to 10 hours, to allow the impregnation solution to penetrate into the pores of the support. If the impregnation solution contains a chemical initiator, after aging, the mixture is preferably heated at one or more temperatures at which the polymerization reaction is initiated. In general, the temperature(s) selected are at or slightly above the temperature required to initiate the polymerization. Control of the heat release during polymerization is recommended to avoid that part of the impregnation solution is expelled from the support pores, reducing the amount of group VI and group VIII metals in the final catalyst. The polymerization reaction can be monitored via the generated exotherm. Once the polymerization reaction is complete, the product is preferably dried to remove the solvent(s). At atmospheric pressure, drying (solvent removal) is preferably at a temperature of about 25° C. to about 200° C., more preferably about 50° C. to about 150° C., and even more preferably about 75° C. to about 125° C. Reduced pressure and / or vacuum conditions may be used for drying. The drying temperature(s) must be below the decomposition temperature of the polymer, which may vary depending on one or more of the catalyst characteristics (support, group VI metal, group VIII metal, and amounts thereof).
[0042] The monomer-containing mixture comprises at least one carrier and at least one monomer species. At least one Group VI metal compound and at least one Group VIII metal compound, or impregnation solution, are optionally included in the carrier and one or more monomer species when forming the monomer-containing mixture. It is recommended and preferred to include a peroxomolybdocobaltate compound or at least one Group VI metal compound and at least one Group VIII metal compound in the monomer-containing mixture. If at least one Group VI metal compound and at least one Group VIII metal compound are not included in the monomer-containing mixture, the impregnation solution can be mixed with the polymerization product of the monomer-containing solution, or the impregnation solution can be contacted with the monomer-containing mixture during polymerization.
[0043] In the process of the present invention, the polymerization of monomer species to form a polymer often uses at least one initiator. Initiators include heat, radiation (e.g., UV), chemicals, and combinations thereof. If the initiator is a chemical, it usually remains on the supported catalyst and may affect the catalyst performance. Therefore, if more than one initiator may be selected, it may be useful to perform tests to determine which combination of initiator(s) and selected monomer(s) allows for optimal catalyst performance. Another consideration is that the selected initiator(s) and monomer(s) do not adversely affect the solubility of the Group VI metal compound and / or Group VIII metal compound in the impregnation solution (e.g., by causing precipitation). For example, in some polymerizations of acrylic acid using persulfates as initiators, potassium persulfate was found to be a better initiator than ammonium persulfate for catalysts containing nickel and molybdenum (see International Patent Publication No. WO2014 / 056846). For the polymerization of acrylamide, when chemical initiators are used, potassium persulfate and ammonium persulfate are preferred initiators. The effectiveness of a particular initiator may vary depending on the concentration of hydrogenation metals present in the catalyst, the monomer, and the conditions under which the catalysis is carried out.
[0044] When the initiator is a chemical (or a chemical in combination with heat or radiation), any suitable chemical initiator can be used that initiates the polymerization of the monomer and does not adversely affect the solubility of the monomer, the group VI metal compound and / or the group VIII metal compound, or the peroxomolybdocobaltate compound present in the solution. Preferred chemical initiators include persulfates such as sodium persulfate, potassium persulfate, and ammonium persulfate, more preferably potassium persulfate and ammonium persulfate. Hydrogen peroxide is a suitable initiator, but it usually needs to be used in a larger amount relative to the monomer compared to the persulfate, at least when the monomer is acrylamide. Furthermore, it has been found that the carrier affects the polymerization when the initiator is hydrogen peroxide, and polymerization is observed when alumina or titanium is the carrier. When silica or a combination of alumina and silica is the carrier, polymerization using hydrogen peroxide as the initiator is not observed. Preferably, when the initiator is hydrogen peroxide, the carrier is alumina, titania, or alumina containing titania, more preferably alumina.
[0045] The suitable initiator also depends on the (polymerization) reactivity of the selected monomer(s). For example, ammonium or potassium persulfate combined with a temperature increase from room temperature to 80° C. is a suitable combination of initiators for the polymerization of acrylic acid or acrylamide. However, for monomers that do not polymerize as easily, a different type of initiator or a different combination of initiators may be required.
[0046] The amount of chemical initiator that provides high yields of polymer may vary depending on the initiator, monomer, metal, and carrier. It has been found that the persulfate is preferably about 1.25 mmol or more, or from about 1.25 mmol to about 3 mmol per mole of monomer, more preferably about 1.5 mmol or more, or from about 1.5 mmol to about 2.75 mmol per mole of monomer, especially when the monomer is acrylamide. By weight, the persulfate is preferably about 0.4% by weight or more, or from about 0.4% by weight to about 1.15% by weight, more preferably about 0.48% by weight or more, or from about 0.48% by weight to about 1.05% by weight, based on the weight of monomer, especially when the monomer is acrylamide.
[0047] In some preferred embodiments, the amount of persulfate that provides a high yield of polymer is about 1.5 mmol or more, preferably about 1.75 mmol or more, even more preferably about 2 mmol or more, and even more preferably about 2.25 mmol or more per mole of monomer, especially when the initiator is ammonium persulfate and especially when the monomer is acrylamide. In other preferred embodiments, the amount of persulfate that provides a high yield of polymer is about 1.5 mmol to about 2.5 mmol, preferably about 1.75 to about 2.5 mmol, more preferably about 2 mmol to about 2.5 mmol, and even more preferably about 2.25 mmol to about 2.5 mmol per mole of monomer, especially when the initiator is ammonium persulfate and especially when the monomer is acrylamide.
[0048] In terms of weight, in some preferred embodiments, the amount of persulfate that provides a high yield of polymer is about 0.48% by weight or more, preferably about 0.55% by weight or more, even more preferably about 0.63% by weight or more, and even more preferably about 0.72% by weight or more, based on the weight of the monomer, especially when the initiator is ammonium persulfate, and especially when the monomer is acrylamide. In other preferred embodiments, the amount of persulfate that provides a high yield of polymer is 0.48% by weight to about 0.8% by weight, preferably about 0.55% by weight to about 0.8% by weight, more preferably about 0.63% by weight to about 0.8% by weight, and even more preferably about 0.72% by weight to about 0.8% by weight, based on the weight of the monomer, especially when the initiator is ammonium persulfate, and especially when the monomer is acrylamide.
[0049] In some other preferred embodiments, the amount of persulfate that provides a high yield of polymer is about 1.9 mmol or more, preferably about 2 mmol or more, even more preferably about 2.25 mmol or more, and even more preferably about 2.5 mmol or more per mole of monomer, especially when the initiator is potassium persulfate and especially when the monomer is acrylamide. In other preferred embodiments, the amount of persulfate that provides a high yield of polymer is about 1.9 mmol to about 3 mmol, preferably about 2 to about 3 mmol, more preferably about 2.25 mmol to about 2.75 mmol, and even more preferably about 2.5 mmol to about 2.75 mmol per mole of monomer, especially when the initiator is potassium persulfate and especially when the monomer is acrylamide.
[0050] In terms of weight, in some other preferred embodiments, the amount of persulfate that provides a high yield of polymer is about 0.75% by weight or more, preferably about 0.8% by weight or more, even more preferably about 0.85% by weight or more, even more preferably about 0.95% by weight or more, based on the weight of the monomer, especially when the initiator is potassium persulfate and especially when the monomer is acrylamide. In other preferred embodiments, the amount of persulfate that provides a high yield of polymer is about 0.75% by weight to about 1.15% by weight, preferably about 0.8% by weight to about 1.15% by weight, more preferably about 0.85% by weight to about 1.05% by weight, even more preferably about 0.95% by weight to about 1.05% by weight, based on the weight of the monomer, especially when the initiator is potassium persulfate and especially when the monomer is acrylamide.
[0051] One of the features of the present invention is that in some cases, the components of the monomer-containing solution can act as initiators for the polymerization reaction when the peroxomolybdocobaltate compound is the source of group VI and group VIII metals. In these cases, the polymerization reaction will only start when the peroxomolybdocobaltate compound and the carrier are present with the monomer. In the absence of either the carrier or the peroxomolybdocobaltate compound, the polymerization will not start without the initiator. Advantageously, this allows for control of the polymerization initiation by excluding either the carrier or, preferably, the peroxomolybdocobaltate compound from the solution until it is desired to start the polymerization reaction. For these initiator-free polymerizations, the carrier is usually alumina, alumina containing silica, alumina containing boria, alumina containing titania, or a mixture of any two or more of these carriers, preferably the carrier is alumina. After impregnation of the support with the peroxomolybdocobaltate compound and monomer, polymerization without chemical initiator, typically at ambient temperature, generally involves heating the impregnated support (monomer-containing solution) to one or more temperatures above about 50°C, preferably from about 50°C to about 100°C.
[0052] For polymerizations in which the combination of peroxomolybdocobaltate compound and support appears to initiate polymerization, supports having an isoelectric point of about 4 or greater at 25° C. are effective. Initiation of polymerization occurred when the support was alumina (isoelectric points of about 7 or 8) and titanium (isoelectric points of about 4 to about 8), but no initiation was observed when the support was silica (isoelectric point of about 1 to about 3).
[0053] The peroxomolybdocobaltate compounds of the present invention generally have a higher amount of cobalt relative to molybdenum than other hydrotreating catalyst systems. In peroxomolybdocobaltates, the Co:Mo ratio is generally about 0.5:2 to about 1.5:2, more preferably about 0.75:2 to about 1.25:2, and even more preferably about 1:2. Peroxomolybdocobaltate compounds are known to be useful in the preparation of Anderson complexes (e.g., Co 3 [Co 2 Mo 10 O 38 H 4 ]), and / or similar portions.
[0054] In the practice of the invention, the peroxomolybdocobaltate compound is prepared by first contacting a molybdenum compound with an oxidizing agent, preferably hydrogen peroxide, to form a molybdenum-containing mixture. The molybdenum compound is dissolved in a polar solvent, the polar solvents and preferences therefor being as described above. In a preferred embodiment, the molybdenum-containing mixture is heated to one or more temperatures ranging from about 30° C. to about 90° C., preferably from about 40° C. to about 80° C., and more preferably from about 50° C. to about 75° C.
[0055] The molybdenum-containing mixture is combined with a cobalt compound to form a molybdenum-cobalt mixture, and the molybdenum-cobalt mixture is spray-dried to obtain a peroxomolybdocobaltate compound. Preferably, the molybdenum-containing mixture is at one or more temperatures ranging from about 30° C. to about 75° C., preferably from about 40° C. to about 65° C., during combination with the cobalt compound. Spray drying is typically carried out at an inlet temperature of about 150° C. or greater, preferably about 180° C., and an outlet temperature of about 100° C.
[0056] Suitable molybdenum and cobalt compounds for forming the peroxomolybdocobaltate compounds, and preferences therefor, when added separately for the catalyst of the present invention, are as described above for the Group VI and Group VIII metal compounds.
[0057] Suitable oxidizing agents for forming peroxomolybdocobaltate include hydrogen peroxide, which may be used at any desired concentration, although solutions having higher concentrations, such as about 30% or greater, are preferred.
[0058] When the oxidizing agent is hydrogen peroxide, the molar ratio of molybdenum to hydrogen peroxide ranges from about 1:4 to about 1:7, preferably from about 1:5 to about 1:6. The molybdenum compound and the cobalt compound are in amounts such that the Co:Mo ratio is from about 0.5:2 to about 1.5:2, more preferably from about 0.75:2 to about 1.25:2, and even more preferably about 1:2.
[0059] As used throughout this specification, the term "support" is used to mean a catalyst support, and the term "support" may be used interchangeably with the term "support". Throughout this specification, the term "support" refers to a support that is in solid form or preformed. Such supports remain primarily in solid form when in contact with a solvent. The term "support" does not refer to precursor salts, such as sodium aluminate, that are nearly completely soluble in one or more solvents, especially polar solvents.
[0060] The support is generally an inorganic oxide, which is carbon and / or a particulate porous solid. Carbon may be used in combination with one or more inorganic oxides, such as alumina, silica, titania, or boria, with silica, especially alumina, being preferred for these combinations. The inorganic oxide support may be made of conventional oxides, such as alumina, silica, alumina containing silica (e.g., silica-alumina, alumina with silica-alumina dispersed therein, alumina-coated silica, silica-coated alumina), alumina containing boria, alumina containing titania, magnesia, zirconia, boria, and titania, as well as combinations of these oxides. Suitable supports also include transition aluminas, such as eta, theta, or gamma alumina. Preferred supports include silica, alumina, silica-alumina, alumina with silica-alumina dispersed therein, alumina-coated silica, or silica-coated alumina, especially alumina or alumina containing up to about 20% by weight silica, preferably up to about 12% by weight silica, more preferably from about 0.25% to about 10% by weight, even more preferably from about 0.5% to about 2% by weight, or from about 5% to about 10% by weight silica. Supports containing transition aluminas, e.g., eta, theta, or gamma alumina, are particularly preferred, with gamma alumina supports being most preferred.
[0061] Another preferred support is an alumina containing boron (or boria) or titanium (or titania), in particular a boria-alumina or titania-alumina. When the alumina contains boron, the boron is preferably B 2 O 3 The amount of titanium is preferably about 0.5% by weight to about 20% by weight, more preferably about 1% by weight to about 15% by weight, and even more preferably about 2% by weight to about 10% by weight. When the alumina contains titanium, the titanium is preferably TiO 2 The amount is preferably about 1% by weight to about 50% by weight, more preferably about 5% by weight to about 30% by weight, and even more preferably about 15% by weight to about 25% by weight.
[0062] The supports are used in a conventional manner, usually in the form of spheres or, preferably, extrudates. Examples of suitable types of extrudates are disclosed in the literature, see, for example, U.S. Pat. No. 4,028,227. Highly suitable for use are cylindrical particles (which may be hollow or solid), as well as symmetrical and asymmetrical polylobed particles (2, 3, or 4 lobes). The support particles are typically calcined at a temperature in the range of about 400° C. to about 850° C. prior to use in forming the catalyst of the present invention.
[0063] To introduce other elements, such as boron, silicon, and / or titanium, into the support, the support may be coextruded with a compound containing the desired atom, co-precipitated with a compound containing the desired atom, or impregnated with a compound containing the desired atom. In the case of coextrusion, the compound is often an oxide or an oxygen-containing acid (e.g., for boron, HBO 2 , H 3 BO 3 , or B 2 O 3 ).
[0064] When other elements such as boron, silicon, and / or titanium are introduced into the inorganic oxide support, typically B 2 O 3 Sufficient boron-containing compound is used to provide about 0.5% to about 20% by weight, preferably about 1% to about 10% by weight, of TiO 2 Sufficient titanium-containing compound is used to provide about 1% to about 50% by weight, more preferably about 5% to about 30% by weight, and even more preferably about 15% to about 25% by weight of SiO 2 Sufficient silicon-containing compound is used to provide from 0.5% to about 15% by weight, preferably from about 0.75% to about 10% by weight, and more preferably from about 0.8% to about 8% by weight of the silicon-containing compound. Preferred supports of this type include alumina containing boron, alumina containing silicon, alumina containing titanium, or a combination of any two or more of these.
[0065] Although no particular pore size is required in the practice of the present invention, the pore volume (N 2 The specific surface area (measured via adsorption) is generally in the range of about 0.25 to about 1 mL / g. The specific surface area is generally in the range of about 50 to about 400 m 2 / g, preferably about 100 to about 300 m 2 / g, more preferably about 150 to about 275 m 2 / g (Braun-Emmet-Teller (BET) N 2 (Measured using adsorption techniques.) Generally, catalysts are 2 The median pore diameter, as determined by adsorption, is in the range of about 5 nm to about 20 nm, preferably in the range of about 6 nm to about 15 nm. Preferably, about 60% or more of the total pore volume is within approximately 2 nm of the median pore diameter. The above pore size distribution and surface area values are determined after calcination of the support at about 500° C. for 1 hour.
[0066] The support particles typically have an average particle size of about 0.5 mm to about 5 mm, more preferably about 1 mm to about 3 mm, and even more preferably about 1 mm to about 2 mm. Because the size and shape of the support are not altered by the process of forming the catalyst, the catalyst generally has an average particle size of about 0.5 mm to about 5 mm, more preferably about 1 mm to about 3 mm, and even more preferably about 1 mm to about 2 mm.
[0067] The amount of support used to form the catalyst of the present invention is from about 40% to about 80% by weight, preferably from about 50% to about 70% by weight, and more preferably from about 60% to about 70% by weight, based on the total weight of the support and the hydrogenation metals, the hydrogenation metals being expressed as their oxides, i.e., excluding solvent and monomer species.
[0068] Methods for impregnating the support are known to those skilled in the art. A preferred method involves co-impregnation of at least one Group VI metal compound and at least one Group VIII metal compound. In the process of the present invention for forming the catalyst, only one impregnation step is required. In a single impregnation step, once the support and the impregnation solution are combined, the mixture is usually homogenized until substantially all of the impregnation solution is incorporated into the catalyst. In this technique, known in the art as pore volume impregnation or incipient wetness impregnation, the impregnation solution is virtually completely incorporated by the pores of the catalyst, which allows for efficient use of chemicals and avoids dust in the product.
[0069] There may be a wide variation in the impregnation method. It is therefore possible to apply multiple impregnation steps, the impregnation solution used containing one or more of the constituent precursors to be deposited, or a part thereof (sequential impregnation). Instead of impregnation techniques, immersion, spraying, etc. methods may be used. When performing multiple impregnation, immersion, etc. steps, drying may be performed between the impregnation steps. However, a single impregnation step is preferred, as it is a faster, simpler process, allows for higher production rates, and is less expensive. A single impregnation also tends to provide a better quality catalyst.
[0070] In a preferred one-step impregnation procedure, a solution having the required concentrations of group VI and group VIII metals is prepared, and then monomer and initiator (if used) are added, preferably at room temperature. More preferably, monomer is added, and then initiator (if used). If necessary, the volume of the impregnation solution containing the metals, monomer, and initiator (if used) is adjusted, usually by dilution, to match the pore volume of the support. If necessary, one or more organic additives may be added at this point. During preparation of the impregnation solution, the temperature of the solution is preferably kept below about 50° C. The impregnation solution is then combined with the support at about 90% to about 105% saturation of its pores, more preferably about 98% to about 100% saturation of its pores. The catalyst is typically aged for several minutes or more at one or more temperatures below about 50° C. After aging, polymerization is induced. In some embodiments, polymerization is induced by heating the catalyst to about 70°C to about 90°C, preferably about 75°C to about 85°C, for about 30 minutes or more. Polymerization can often be monitored by measuring the exotherm released during polymerization. Once polymerization is complete, the catalyst is typically dried at one or more temperatures from about 50°C to about 150°C, preferably from about 50°C to about 80°C.
[0071] In a preferred two-step impregnation procedure, a solution having the required concentrations of group VI and group VIII metals is prepared, and then, if necessary, the volume of the metal-containing impregnation solution is adjusted, usually by dilution, to match the pore volume of the support. This solution is combined with the support, and the resulting solid is dried at one or more temperatures from about 50°C to about 150°C, preferably from about 50°C to about 80°C. In the second impregnation step, a solution containing monomer and initiator (if used) is prepared in deionized water. The monomer-containing solution is combined with the metal-impregnated support at about 90% to about 105% saturation of its pores, more preferably about 98% to about 100% saturation of its pores. The metal-impregnated support is typically aged for about 60 minutes or more at one or more temperatures below about 50°C, more preferably below about 40°C. After aging, polymerization is induced. In some embodiments, polymerization is induced by heating the catalyst to about 70°C to about 90°C, preferably about 75°C to about 85°C, for about 30 minutes or more. Polymerization can often be monitored by measuring the exotherm released during polymerization. Once polymerization is complete, the catalyst is typically dried at one or more temperatures from about 50°C to about 150°C, preferably from about 50°C to about 80°C.
[0072] When at least one Group VI metal compound and at least one Group VIII metal compound form part of a monomer-containing mixture, polymerization of the monomer species is preferably carried out after the impregnation step, although polymerization may begin during impregnation of the support. When polymerization is carried out after impregnation, polymerization may be carried out before or during removal of excess solvent, if removal of excess solvent is carried out, preferably polymerization may be carried out before removal of excess solvent. Similarly, when the impregnation solution and the support are combined to form an impregnated support that is then mixed with the monomer, polymerization is preferably carried out before removal of excess solvent, if removal of excess solvent is carried out. It is recommended and preferred to minimize evaporation of the solvent during the polymerization step.
[0073] In the process of the present invention, polymerization can be carried out in the usual manner by exposing the monomer species to an initiator in an amount suitable to polymerize at least a portion of the monomer. Polymerization can be carried out without an initiator by heating the monomer-containing solution to about 50° C. or higher when both the metal and the support are present and at least a portion of the metal is in the form of a peroxomolybdocobaltate compound. Whether or not an initiator is used, the polymerization inhibitor needs to be inactivated if it is to start the polymerization reaction.
[0074] If the at least one Group VI metal compound and the at least one Group VIII metal compound do not form part of the monomer-containing mixture, polymerization is initiated in the presence of the support prior to impregnation, and the impregnation solution is mixed with the monomer-containing mixture during or after polymerization is completed.
[0075] The polymer in the catalyst has a carbon skeleton and contains functional groups with one or more lone pairs of electrons. Preferably, the functional groups of the monomer species contain nitrogen, oxygen, phosphorus, and / or sulfur. Examples of suitable functional groups include hydroxyl groups, carboxyl groups, carbonyl groups, amino groups, amide groups, nitrile groups, amino acid groups, phosphate groups, thiol groups, sulfonic acid groups, etc. Preferred functional groups include hydroxyl groups, ester groups, amide groups, and carboxyl-containing groups, especially carboxylic acid groups, more preferably carboxylic acid groups and amide groups, especially amide groups.
[0076] Examples of polymers formed as part of the catalyst of the present invention include polyacrylic acid, polymaleic acid, polyfumaric acid, polycrotonic acid, poly(pentenoic) acid, polymethacrylic acid, polydimethacrylic acid, poly(allyl alcohol), poly(2-sulfoethyl)methacrylate, poly(n-propyl)acrylate, poly(hydroxymethyl)acrylate, poly(2-hydroxyethyl)acrylate, poly(2-carboxyethyl)acrylate, poly(3-ethoxy-3-oxopropyl)acrylate, poly(methylcarbamylethyl)acrylate, poly(2-hydroxyethyl)methacrylate, polyvinylpyrrolidone, poly(phenylene)acrylate ... Examples of suitable polymers include, but are not limited to, acrylamide, polymethacrylamide, poly(N-isopropyl)acrylamide, polyvinylacetamide, polyvinyl-N-methylacetamide, poly(N-hydroxymethyl)acrylamide, poly(N-hydroxyethyl)acrylamide, poly(N-methoxymethyl)acrylamide, poly(N-ethoxymethyl)acrylamide, polyvinyl sulfate, polyvinyl sulfonic acid, poly(2-propyl)-1-sulfonic acid, polyvinyl phosphate, polyvinyl phosphonic acid, poly(dimethylallyl phosphate), poly(diethylallyl phosphate), polyvinyl phosphonic acid, etc. Preferred polymers include polyacrylic acid, polymaleic acid, polyfumaric acid, poly(2-carboxyethyl)acrylate, polyacrylamide, and poly(N-hydroxyethyl)acrylamide, more preferably polyacrylamide and polyacrylic acid, especially polyacrylamide. As noted above, more than one monomer type may be used, and in such cases the polymer formed will be a copolymer, which may be a copolymer of any two or more of the polymers listed above.
[0077] The monomers used to form the supported catalyst are often soluble in the solvent, but the polymer formed from the monomer(s) does not need to be soluble in the solvent(s) used to form the catalyst.
[0078] The process of the invention results in a supported catalyst in which the Group VIII metal is typically present in an amount of from about 1 to about 10 weight percent, preferably from about 3 to about 8.5 weight percent, calculated as the monoxide. When the Group VI metal in the catalyst is molybdenum, it is typically present in an amount of up to about 35 weight percent, preferably from about 15 to about 35 weight percent, calculated as molybdenum trioxide.
[0079] If at least one Group VI metal compound and at least one Group VIII metal compound, or an impregnation solution, is included before or during the polymerization, a supported catalyst is obtained at the end of the polymerization step. If, instead, a polymerization product is formed and then contacted with an impregnation solution after polymerization, a supported catalyst is obtained at the end of the impregnation step(s).
[0080] Optionally, excess solvent is removed from the supported catalyst. The removal of excess solvent may be carried out in air, under vacuum, or in the presence of an inert gas. The removal of the solvent is preferably achieved by drying the supported catalyst. The drying of the supported catalyst is carried out under conditions such that at least a portion of the polymer remains in the catalyst, i.e., the polymer is not completely removed by decomposition. The drying conditions applied therefore depend on the temperature at which the particular polymer decomposes, which may include combustion if the drying is carried out in the presence of oxygen. In these processes of the invention, the drying should be carried out under conditions such that after drying, about 50% or more, preferably about 70% or more, more preferably about 90% or more of the polymer is still present in the catalyst. It is preferred to retain as much polymer as possible in the supported catalyst during drying, although it is understood that at least in the case of polymers that are prone to decomposition, loss of some of the polymer during the drying step cannot always be avoided. Depending on the polymer, a drying temperature of less than about 270° C. may be necessary. In some embodiments, the drying temperature is preferably from about 25° C. to about 200° C., more preferably from about 50° C. to about 150° C., and even more preferably from about 75° C. to about 125° C., and the drying temperature(s) should be below the decomposition temperature of the polymer. Reduced pressure and / or vacuum conditions may be used for drying.
[0081] As described above, the supported catalyst of the present invention comprises a support, at least one Group VI metal, at least one Group VIII metal, and a polymer, the molar ratio of the Group VI metal to the Group VIII metal being from about 1:1 to about 5:1, and the polymer having a carbon skeleton and containing a functional group having at least one heteroatom. The support and preferences thereof are as described above. The support in the supported catalyst of the present invention is in an amount of from about 40% to about 80% by weight, preferably from about 50% to about 70% by weight, more preferably from about 60% to about 70% by weight, based on the total weight of the support and the hydrogenation metals, and the hydrogenation metals are expressed as their oxides, i.e., excluding the polymer. The hydrogenation metals and preferences thereof are accordingly as described above. In the polymer, the carbon skeleton may also be referred to as a carbon-carbon skeleton, and the skeleton is the main chain of the polymer. The polymer in the supported catalyst and preferences thereof are as described above.
[0082] Optionally, the catalyst of the present invention may be subjected to a sulfiding step (treatment) to convert the metal components to their sulfides. In the context of this specification, the phrases "sulfiding step" and "sulfidation step" are meant to include any process step in which a sulfur-containing compound is added to the catalyst composition and at least a portion of the hydrogenation metal components present in the catalyst are converted to sulfide form either directly or after an activation treatment with hydrogen. Suitable sulfidation processes are known in the art. The sulfiding step may be carried out ex situ, in situ, or a combination of ex situ and in situ to the reactor in which the catalyst is used for hydrotreating the hydrocarbon feed.
[0083] Ex situ sulfurization processes are carried out outside the reactor in which the catalyst is used for hydrotreating the hydrocarbon feed. In such processes, the catalyst is contacted with a sulfur compound, such as an organic or inorganic polysulfide or elemental sulfur, outside the reactor and, if necessary, dried, preferably in an inert atmosphere. In a second step, the material is treated with hydrogen gas in the reactor at elevated temperature, optionally in the presence of the feed, to activate the catalyst, i.e., to bring it to the sulfided state.
[0084] The in situ sulfurization process is carried out in a reactor in which the catalyst is used for hydrotreating the hydrocarbon feed. Here, the catalyst is contacted in the reactor at high temperature with a hydrogen gas stream mixed with a sulfurizing agent such as hydrogen sulfide or a compound decomposable to hydrogen sulfide under prevailing conditions (e.g. dimethyl disulfide). It is also possible to use a hydrogen gas stream combined with a hydrocarbon feed containing sulfur compounds decomposable to hydrogen sulfide under prevailing conditions. In the latter case, it is possible to sulfurize the catalyst by contacting it with a hydrocarbon feed containing an added sulfurizing agent such as dimethyl disulfide (spiked hydrocarbon feed), and it is also possible to use a sulfur-containing hydrocarbon feed without added sulfurizing agent, since the sulfur components present in the feed are converted to hydrogen sulfide in the presence of the catalyst. A combination of the various sulfurization techniques can also be applied. The use of a spiked hydrocarbon feed may be preferred.
[0085] When the catalyst is subjected to an in-situ sulfurization step, the catalyst is exposed to high temperatures in the presence of oil and water formed during the process before sulfurization is completed. This exposure to high temperatures in the presence of oil and water does not appear to adversely affect the catalytic activity. Without wishing to be bound by theory, it is believed that the polymer is more resistant to leaching or evaporation compared to catalysts described in the art that have low molecular weight organic additives.
[0086] The catalyst compositions of the present invention are produced by the processes described above, whether or not the processes include the optional sulfiding step.
[0087] Without wishing to be bound by theory, both the observed better dispersion of the hydrogenation metals and the weak (low) metal-support interaction are achieved by forming a polymer in the supported catalyst using monomers with functional groups as described above. It is hypothesized that such a polymer helps to distribute the hydrogenation metals throughout the pore network. Also, without wishing to be bound by theory, it is believed that the hydrogenation metals interact with the polymer, which distributes the hydrogenation metals in the pore space of the support. It is also hypothesized that activation of the catalyst in a sulfurizing atmosphere replaces at least a portion of the heteroatoms of the functional groups of the polymer with sulfur, which is believed to help minimize or prevent the hydrogenation metals from clustering together or interacting with the support, which is believed to minimize clustering and / or interacting with the support, which in turn contributes to the observed enhanced catalytic activity. In addition, it is theorized that the polymer (after sulfurization) may inhibit sintering of the hydrogenation metals, contributing to the improved stability of the supported catalyst.
[0088] The catalyst composition of the present invention may be used for the hydrotreating, hydrodenitrogenating, and / or hydrodesulfurizing of a wide range of hydrocarbon feeds. Examples of suitable feeds include middle distillates, kerosene, naphtha, vacuum gas oil, heavy gas oil, etc.
[0089] The process of the invention is a process for the hydrotreating, hydrodenitrogenating, and / or hydrodesulfurizing of a hydrocarbon feed, which process comprises contacting the hydrocarbon feed with a catalyst of the invention. Hydrotreating a hydrocarbon feed involves treating the feed with hydrogen at hydrotreating conditions and in the presence of the catalyst composition of the invention.
[0090] Temperatures in the range of about 250°C to about 450°C, pressures of about 5 to about 250 bar (about 5x10 5 Pa ~ approx. 2.5x10 7The reactor inlet hydrogen partial pressure is in the range of about 0.1 to about 10 vol. / vol.hr, and the H 2 Conventional hydrotreating process conditions, such as feed / stream ratio, may be applied.
[0091] As shown in the examples, polymer loadings of up to at least 20 wt.% relative to the other catalyst components have been achieved. The amount of polymer present in the supported catalyst (polymer loading) is defined in the same manner as the amount of monomer relative to the other catalyst components defined above. In other words, the amount of polymer in the catalyst of the present invention is expressed as weight % relative to the total weight of the other components used to form the catalyst, excluding any solvent. For example, if the total weight of the other components of the catalyst is 100 grams, then 10 wt.% of polymer is 10 grams. In the present invention, the polymer loading is generally about 1.5 wt.% or more, preferably in the range of about 1.5 wt.% to about 35 wt.%, relative to the total weight of the other components in the catalyst, including the support, the Group VI metal, and the Group VIII metal, although amounts outside these ranges are within the scope of the present invention, where the Group VI metal and the Group VIII metal are expressed as their oxides, and the weight of any solvent is excluded. The amount of polymer loaded is more preferably in the range of about 3% to about 30% by weight, even more preferably in the range of about 5% to about 25% by weight, and even more preferably in the range of about 10% to about 25% by weight, based on the total weight of the other components of the catalyst, particularly when the polymer is polyacrylic acid or polyacrylamide. EXAMPLES
[0092] The following examples are presented for illustrative purposes and are not intended to impose limitations on the scope of the invention.
[0093] In some examples below, carbon yield (C yield) is reported, defined as the % of carbon introduced into the sample via the monomer that is still present after drying of the material.
[0094] In some cases, catalyst activity is reported as relative gravimetric activity (RWA). Relative gravimetric activities for both hydrodesulfurization (HDS) and hydrodenitrogenation (HDN) are reported relative to a comparison run, where the catalyst activity of the comparison run is set to an arbitrary value (e.g., 100) and the RWA of the tested catalyst is reported as a multiple of the value of the comparison catalyst run.
[0095] Example 1 A stock supply of peroxomolybdocobaltate (i.e., containing cobalt and molybdenum, but no phosphorus) was first prepared by adding MoO 3 (168.2g), H 2 O 2 (aqueous, 30%, 648 g), water (581.5 g), Mo:H 2 O 2 The mixture was prepared by mixing them together in a ratio of 1:5-6 and heating to 70 °C. An exothermic reaction occurred around this temperature, probably due to the formation of peroxomolybdocobaltate. After the exotherm subsided, the mixture was cooled to 50-60 °C. Cobalt carbonate (CoCO 3 , 74.4 g, equivalent to 43.5 g CoO) was added and the mixture was stirred for at least 1 hour. Evaporation of water to form a more concentrated solution resulted in the formation of an insoluble sediment, indicating that the solution could not be concentrated by simple evaporation, so the solution was concentrated by spray drying to obtain a solid. No monomer or initiator was present in this stock supply of peroxomolybdocobaltate. The desired concentrations of cobalt and molybdenum for impregnation were prepared by dissolving the spray-dried solids in water.
[0096] Example 2 Several samples were prepared from alumina and acrylamide using different polymerization initiators and / or different amounts of polymerization initiator. The acrylamide was 20% by weight based on the weight of the combined monomer and carrier. After polymerization, the samples were dried at 80°C. The samples were analyzed by evolved gas analysis (EGA) at 600°C under helium. Some of the compounds produced by heating were acrylonitrile and acrylamide, which are known to be toxic. The polymer yield, as well as the carbon yield, were calculated by dividing the amount of carbon remaining after EGA treatment by the amount of carbon in the dried product, and the polymer yields are reported in Table 1 below. [Table 1]
[0097] The effect of the carrier on polymerization when hydrogen peroxide is the initiator has been noted and is theorized to be a pH effect, although this is not certain.
[0098] Example 3 Some samples were prepared from water and a stock supply of peroxomolybdocobaltate prepared in Example 4, with 5.4 wt. % CoO and 5.4 wt. % MoO in solution. 3 The metal-containing solutions were prepared in amounts that provided 26 wt. % as impregnation. Acrylamide (AAM), alumina, and in one run, potassium persulfate (PPS) were mixed with the metal-containing solution. After impregnation and aging, each mixture was heated at 80° C. and monitored for the presence of an exotherm. An exotherm indicates the occurrence of a polymerization reaction. The results are summarized in Table 2. Runs 11C and 12C are comparative. [Table 2]
[0099] The results in Table 2 indicate that peroxomolybdocobaltate alone does not cause polymerization; both peroxomolybdocobaltate and alumina or initiator must be present to effect polymerization.
[0100] For the one-step impregnation procedure, a solution with the required concentration of molybdenum and cobalt was prepared from either molybdenum and cobalt compounds or from a peroxomolybdocobaltate compound. The monomer was then added at room temperature, followed by the initiator (if used). The volume of the impregnation solution containing the metals and monomer, as well as phosphorus and / or initiator, if used, was then adjusted to 100% of the support pore volume by dilution with deionized water. If necessary, organic additives may be added at this point. The temperature of the solution was kept below 50°C during the preparation of the solution for the one-step impregnation procedure to prevent polymerization in the solution before impregnation is complete. The final solution should be a clear liquid. The final solution was then introduced onto the alumina extrudates at 90-105% saturation of its pores. The catalyst was aged below 50°C for at least 60 minutes to ensure homogeneous dispersion of the solution throughout the alumina extrudates without inducing polymerization. After aging, polymerization was induced by heating the catalyst at 70-90 °C for at least 30 min. Polymerization was monitored by measuring the exotherm released during polymerization. Once polymerization was complete, the catalyst was dried at temperatures between 50-150 °C to remove excess water.
[0101] For the two-step impregnation procedure, a solution with the required concentrations of molybdenum and cobalt was prepared as described for the one-step procedure, except that the monomer and initiator (if used) were not present in the solution. This solution was combined with the alumina extrudates and dried as described above. In the second impregnation step, a solution containing the monomer and, if used, the initiator was prepared in deionized water. The monomer-containing solution was introduced into the metal-impregnated alumina extrudates at 90-105% saturation of their pores. The catalyst was aged at 40°C for at least 60 minutes and then polymerized by heating the catalyst at 70-90°C for at least 30 minutes. The polymerization was monitored by measuring the exotherm released during the polymerization. Once the polymerization was complete, the catalyst was dried at a temperature of 50-150°C to remove excess water.
[0102] In some of the following examples, diethylene glycol (DEG) was used in the comparison solution because DEG is considered to be a state-of-the-art additive, see U.S. Patent Nos. 6,753,291 and 6,923,904 in this regard.
[0103] Example 4 Preparation of polymer-modified catalysts containing Co and Mo The catalysts for all runs in this example were prepared using the one-step impregnation method described above and a portion of the stock supply of peroxomolybdocobaltate prepared in Example 1. Some samples were made using acrylamide (AAM) and a portion of the stock solution (Runs 15, 16, and 17). To prepare the samples, a certain amount of the stock solution was weighed into a round-bottom flask. Some of the samples did not contain acrylamide. Acrylamide (and in some cases potassium persulfate, PPS) was added at the appropriate point in the impregnation procedure. 271m 2 γ-alumina extrudates with a surface area of 1 / g were used as the support. The amounts of reagents and some of the catalyst properties are listed in Table 3 below. In Table 3, the amounts of Co, Mo, and alumina are reported relative to the total weight of the support and hydrogenation metals, the amounts of monomer, initiator, and organic additives are relative to the total (dry) weight of the catalyst, which is calculated as MoO 3 , CoO, monomer, initiator, but no organic additive. The organic additive was diethylene glycol (DEG). Runs 15C and 16C are comparisons.
[0104] In a comparative run (19C), a solution of acrylamide and alumina was made and heated to 80° C. No exotherm was observed, which was interpreted as indicating that polymerization had not occurred. In another comparative run (18C), a solution of molybdenum, cobalt, and acrylamide was made and heated to 80° C. No exotherm was observed, which was interpreted as indicating that polymerization had not occurred. In contrast, exotherms were observed for Run 16 (15° increase) and Run 17 (10° increase). [Table 3]
[0105] FIG. 1 shows the FT-IR spectrum of a catalyst of the present invention similar to that of Run 17 (solid line, no initiator), and a comparative run similar to Run 17 but containing phosphorus (dashed line). This comparative sample showed no signs of polymerization such as an exotherm during preparation. In addition, some characteristics of acrylamide were observed at 1430 cm based on a comparison with the literature (Journal of the Korean Physical Society, 1998, 32, 505-512). -1 Acrylamide CN stretch at 1053cm -1 -CH in 2 -rocking (dashed line) can be recognized in the FT-IR spectrum of the comparative sample. For the catalyst of the present invention similar to that of run 17, the FT-IR spectrum (solid line) shows a peak at 1612 cm -1 The disappearance of characteristic acrylamide signals such as the CC stretch at 1465 cm -1 -CH in 2 -Deformation and 1420cm -1 The appearance of polyacrylamide signals such as C-N stretches at 1000 nm suggests successful polymerization. The heterogeneity of these catalysts hampers their complete characterization.
[0106] Example 5 Activity test of catalysts containing Co and Mo The catalyst prepared as described in Example 3 was ground and the 125-310 μm powder fraction was isolated by sieving. The 125-310 μm fraction was evaluated for their performance in hydrodesulfurization and hydrodenitrogenation. The catalyst was sulfided by contacting it with dimethyl disulfide (2.5 wt% S), spiked straight run gas oil (SRGO) immediately before running the test. The presulfiding conditions are listed in Table 4A. The catalyst test was carried out using a high throughput test unit (HTU). SRGO feed with a density of 0.849 g / mL at 15° C., a sulfur content of 13713 ppm, and a nitrogen content of 121 ppm was used for the test. The three different conditions used for the test are listed in Table 4B. [Table 4] [Table 5]
[0107] Several periodic wastewater samples were taken during each test condition. Table 5 lists the average S and N values at each test condition, which are the average of several samples, as well as the relative gravimetric activities (RWA) of the different catalysts. The relative gravimetric activities for both hydrodesulfurization (HDS) and hydrodenitrogenation (HDN) are reported relative to a comparison run, where the catalyst activity of the comparison run is set to an arbitrary value (e.g., 100) and the RWA of the catalyst being tested is reported as a multiple of the value of the comparison catalyst run. In these runs, the RWA from the run using the polymer-containing catalyst is given relative to the RWA from the run using the DEG-containing catalyst normalized to 100%. A significant increase in catalyst activity can be achieved for catalysts containing polyacrylamide compared to catalysts containing diethylene glycol where the catalyst composition is otherwise the same (see Table 5). The increase in HDS activity on a weight basis is about 10% to about 20% by weight, depending on the test conditions and catalyst composition. Runs 15C and 16C are comparisons, run 15C is a comparison against run 15 and run 16C is a comparison against runs 16 and 17. [Table 6]
[0108] Example 6 Preparation of polymer-modified catalysts containing Co and Mo Following the procedure of Example 4, catalyst samples containing Co and Mo with acrylamide (AAM) were prepared using a portion of the stock supply of peroxomolybdocobaltate prepared in Example 4 and an extruded alumina support. The alumina support portion contained boron, silicon, or titanium, with boron being introduced by coextrusion with alumina, titanium being introduced by impregnation, and silicon being introduced by coprecipitation. The coextrusion procedure is described, for example, in International Patent Publication No. WO2010 / 121807. The catalysts for all runs in this example were prepared using the one-step impregnation method described above. Some of the amounts of reagents and catalyst properties are listed in Table 6. In Table 6, the amounts of Co, Mo, and alumina are reported relative to the total weight of the support, hydrogenation metal, and phosphorus, and the amounts of monomer, initiator, and organic additives are reported relative to the total weight of the alumina, MoO 3 , and relative to the total (dry) weight of CoO. [Table 7]
[0109] Samples from the runs listed in Table 6 were subjected to scanning electron microscope energy dispersive X-ray (SEM-EDX) line scan analysis. Each sample was dried at 150° C. under vacuum (approximately 0.05 mbar) for 24 hours and then embedded in epoxy resin (EpoFix, Struers Inc.) at atmospheric pressure. The resin was pre-cured for approximately 70 minutes before the embedding procedure to avoid as much as possible (less than 5 μm) penetration of the resin into the extrudates. The embedded samples were ground and polished under nitrogen to minimize exposure of the samples to the atmosphere and then coated with a gold layer to a thickness of approximately 2 nm. Line scan measurements were performed using a scanning electron microscope (Zeiss EVO MA 15 with Noran system 7, light source: LaB 6 The experiment was performed with a beam current of 4.2 nA.
[0110] The results are shown in Figures 2-1 through 2-3 as grams of element per 100 grams of support (here alumina). Because the weight of pure support per unit of volume across a cross section of the extrudate (support) does not change regardless of the weight of the element impregnated, the grams of element indicate whether the element is present throughout the support or only on its surface. Note that the scale of the elements on the left side of the line scan graph is much smaller than the scale of the elements on the right side of the line scan graph. The distribution of carbon and nitrogen in the graphs is relatively flat, indicating that polymer is formed throughout the support in runs A through F.
[0111] An ingredient referred to by chemical name or formula anywhere in this specification or claims, whether referred to in the singular or plural, is identified as being present prior to contact with another substance referred to by chemical name or chemical type (e.g., another ingredient, solvent, etc.). It does not matter what chemical changes, transformations, and / or reactions (if any) occur in the resulting mixture or solution, because such changes, transformations, and / or reactions are the natural result of bringing together the particular ingredients under the conditions required in accordance with this disclosure. Thus, ingredients are identified as components that are brought together in connection with performing a desired operation or in forming a desired composition. Also, even if the claims below may refer to substances, ingredients, and / or components in the present tense (such as "comprising," "is," etc.), the reference refers to the substance, ingredient, or component that was present immediately prior to being first contacted, blended, or mixed with one or more other substances, ingredients, and / or components in accordance with this disclosure. Thus, the fact that a substance, component, or ingredient may have lost its original identity through chemical reaction or chemical transformation in the course of a contacting, blending, or mixing operation when carried out in accordance with this disclosure and within the ordinary skill of a chemist, is of no practical importance.
[0112] The present invention may comprise, consist of, or consist essentially of the materials and / or procedures recited herein.
[0113] As used herein, the term "about" modifying the amount of an ingredient in the composition or used in the method of the present invention refers to possible variations in the numerical amount, such as through typical measuring procedures and liquid handling procedures used to make concentrates or use solutions in the real world, through inadvertent errors in these procedures, through differences in manufacture, source, or purity of ingredients used to make the composition or carry out the method. The term about also encompasses amounts that differ due to different equilibrium conditions of the composition obtained from a particular initial mixture. Whether or not modified by the term "about", the claims include the equivalent of the amount.
[0114] Unless expressly indicated otherwise, the article "a" or "an" as used herein is not intended, and should not be construed as, limiting the description or claims to the single element to which the article refers. Rather, the article "a" or "an" as used herein is intended to cover one or more such elements, unless the context expressly indicates otherwise.
[0115] This invention is susceptible to considerable variation in its practice, and therefore the foregoing description is not intended to limit, and should not be construed as limiting, the invention to the particular exemplifications presented hereinabove.
Claims
1. 1. A supported catalyst comprising a support, at least one Group VI metal, at least one Group VIII metal, and a polymer, wherein the molar ratio of said Group VI metal to said Group VIII metal is from about 1:1 to about 5:1, and said polymer has a carbon backbone and comprises a functional group having at least one heteroatom.
2. 2. The supported catalyst of claim 1, wherein the support is carbon, carbon in combination with one or more inorganic oxides, boria, titania, silica, alumina, silica-alumina, alumina having silica-alumina dispersed therein, alumina-coated silica, silica-coated alumina, alumina containing boron, alumina containing silicon, alumina containing titanium, or a combination of any two or more thereof.
3. 2. The supported catalyst of claim 1, wherein the functional group of the polymer is a carboxylic acid group or an amide group.
4. 2. The supported catalyst of claim 1, wherein the polymer is polymaleic acid, polyfumaric acid, polyacrylic acid, poly(2-carboxyethyl)acrylate, poly(N-hydroxyethyl)acrylamide, polyacrylamide, or a copolymer of any two or more of the foregoing.
5. 2. The supported catalyst of claim 1, wherein the Group VI metal is molybdenum and / or tungsten and / or the Group VIII metal is nickel and / or cobalt.
6. 2. The supported catalyst of claim 1 having a polymer loading of about 1.5 wt. % or greater, based on the total weight of the support, the Group VI metal, and the Group VIII metal, wherein the Group VI metal and the Group VIII metal are expressed as their oxides.
7. 10. The supported catalyst of claim 1 having an average particle size of about 0.5 mm to about 5 mm.
8. 2. The supported catalyst of claim 1, wherein the support is about 40% to about 80% by weight, based on the total weight of the support, the Group VI metal, and the Group VIII metal, and the Group VI metal and the Group VIII metal are expressed as their oxides.
9. 3. The supported catalyst of claim 2, wherein the support is carbon, or alumina containing boron, alumina containing silicon, and / or alumina containing titanium.
10. 1. A process for forming a supported catalyst comprising: I) A carrier, one or more monomer species, a solvent, and a peroxomolybdocobaltate compound or at least one Group VI metal compound and at least one Group VIII metal compound in the following combination: a) a carrier, one or more monomer species, and a solvent; b) a support, one or more monomeric species, and a peroxomolybdocobaltate compound or at least one Group VI metal compound and at least one Group VIII metal compound; or c) combining a support with an impregnation solution to form an impregnated support, and then combining the impregnated support with one or more monomer species; forming a monomer-containing mixture, the one or more monomer species being soluble in the solvent and having at least one functional group containing carbon-carbon unsaturation and at least one heteroatom; II) initiating polymerization of at least a portion of the one or more monomer species in the monomer-containing mixture to form a polymerization product; III) When the monomer-containing mixture in I) is formed similarly to a), A) by contacting the monomer-containing mixture with an impregnation solution during the polymerization in II); or B) contacting the polymerization product with an impregnation solution, forming a supported catalyst, wherein the molar ratio of the Group VI metal to the Group VIII metal is from about 1:1 to about 5:1, and the impregnation solution comprises a solvent, at least one Group VI metal, and at least one Group VIII metal.
11. A single impregnation step a) In I), when the support, one or more monomer species, and the peroxomolybdocobaltate compound or at least one Group VI metal compound and at least one Group VIII metal compound are combined, b) in I), when the support and the impregnation solution are combined; or The process according to claim 10, wherein in step c) III) is carried out.
12. The process of claim 10, further comprising removing excess solvent from the supported catalyst.
13. The process of claim 12 wherein the polymerization is carried out during removal of the excess solvent.
14. The process of claim 10 further comprising sulfiding the supported catalyst.
15. 11. The process of claim 10, wherein the monomer-containing mixture in I) is formed similarly to b).
16. The process of claim 10 , wherein the heteroatoms of the functional groups of the monomeric species comprise nitrogen, oxygen, phosphorus, and / or sulfur.
17. The process of claim 10, wherein the functional group of the monomeric species is a carboxylic acid group, an ester group, a carboxyl group, or an amide group.
18. The process of claim 10, wherein the monomer species is maleic acid, fumaric acid, acrylic acid, 2-carboxyethyl acrylate, acrylamide, or N-hydroxyethylacrylamide.
19. 11. The process of claim 10, wherein the monomer species is acrylic acid or acrylamide.
20. 11. The process of claim 10, wherein the monomer species is in an amount of about 1.5 wt. % or greater, based on the total weight of the support, the Group VI metal compound, and the Group VIII metal compound, and wherein the Group VI metal compound and the Group VIII metal compound are expressed as oxides.
21. 11. The process of claim 10, wherein the support is carbon, boria, titania, silica, alumina, silica-alumina, alumina having silica-alumina dispersed therein, alumina-coated silica, silica-coated alumina, alumina containing boria, and / or alumina containing titania.
22. 11. The process of claim 10, wherein a chemical is used as an initiator, said chemical comprising a persulfate.
23. 16. The process of claim 15, wherein the solvent is water.
24. 16. The process of claim 15, wherein the Group VI metal compound is an oxide or an oxoacid.
25. 16. The process of claim 15, wherein the Group VIII metal compound is a carbonate, hydroxide, or hydroxycarbonate.
26. 24. The process of claim 23, wherein the Group VI metal compound is a molybdenum compound and / or a tungsten compound and / or the Group VIII compound is a nickel and / or a cobalt compound.
27. 11. The process of claim 10, wherein a peroxomolybdocobaltate compound is used and the support is alumina, alumina containing silica, alumina containing boria, alumina containing titania, or a mixture of any two or more thereof.
28. 11. The process of claim 10, wherein the support is calcined and / or extruded prior to step I) of the process.
29. The process of claim 10, wherein the support has an average particle size of from about 0.5 mm to about 5 mm and the supported catalyst has an average particle size of from about 0.5 mm to about 5 mm.
30. 27. The process of claim 26, wherein the support is an alumina containing boron, an alumina containing silicon, an alumina containing titanium, or a combination of any two or more thereof.
31. 11. The process of claim 10, wherein the monomer-containing mixture in I) is formed similar to b) or c) and the support is alumina, alumina containing silica, alumina containing boria, alumina containing titania, or a mixture of any two or more thereof, and the polymerization is initiated by heating the monomer-containing mixture to one or more temperatures of about 50° C. or greater.
32. 1. A process for forming a peroxomolybdocobaltate compound, comprising: i) combining at least one molybdenum compound and at least one oxidizing agent in a polar solvent to form a molybdenum-containing mixture; ii) combining the molybdenum-containing mixture with at least one cobalt compound to form a molybdenum-cobalt mixture with a cobalt:molybdenum ratio of about 0.5:2 to about 1.5:2; ii) spray drying the molybdenum-cobalt mixture to obtain the peroxomolybdocobaltate compound.
33. 33. The process of claim 32, wherein the oxidizing agent is hydrogen peroxide.
34. 34. The process of claim 33, wherein the molar ratio of molybdenum to hydrogen peroxide ranges from about 1:4 to about 1:
7.
35. 35. The process of any one of claims 32 to 34, wherein the molybdenum compound is molybdenum oxide and / or the cobalt compound is cobalt carbonate.
36. 33. The process of claim 32, wherein the cobalt:molybdenum ratio is from about 0.75:2 to about 1.25:2.
